A rapid ATR-FTIR spectroscopic method for detection of sibutramine adulteration in tea and coffee based on hierarchical cluster and principal component analyses - Cebi, Nur; Yilmaz, Mustafa Tahsin; Sagdic, Osman (ELSEVIER SCI LTD, 2017)
Sibutramine may be illicitly included in herbal slimming foods and supplements marketed as 100% natural to enhance weight loss. Considering public health and legal regulations, there is an urgent need for effective, rapid and reliable techniques to detect sibutramine in dietetic herbal foods, teas and dietary supplements. This research comprehensively explored, for the first time, detection of sibutramine in green tea, green coffee and mixed herbal tea using ATR-FTIR spectroscopic technique combined with chemometrics. Hierarchical cluster analysis and PCA principle component analysis techniques were employed in spectral range (2746-2656 cm(-1)) for classification and discrimination through Euclidian distance and Ward's algorithm. Unadulterated and adulterated samples were classified and discriminated with respect to their sibutramine contents with perfect accuracy without any false prediction. The results suggest that existence of the active substance could be successfully determined at the levels in the range of 0.375-12 mg in totally 1.75 g of green tea, green coffee and mixed herbal tea by using FTIR-ATR technique combined with chemometrics. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Sibutramine; ATR-FTIR; Chemometrics; Adulteration; Slimming tea; DIETARY-SUPPLEMENTS; INFRARED-SPECTROSCOPY; IDENTIFICATION; CLASSIFICATION; FORMULATIONS; HONEY; HPLC; Chemistry; Food Science & Technology; Nutrition & Dietetics